Effects of underweight and overweight on mortality in patients with pulmonary tuberculosis - Min, Jinsoo; Kim, Ju Sang; Kim, Hyung Woo; Ko, Yousang; Oh, Jee Youn; Jeong, Yun-Jeong; Lee, Eun Hye; Yang, Bumhee; Lee, Ki Man; Ahn, Joong Hyun; Kim, Jin Woo; Hwang, Yong Il; et al. (Frontiers in Public Health, 2023)
Background: Poor nutrition increases disease severity and mortality in patients with tuberculosis (TB). There are gaps in our understanding of the effects of being underweight or overweight on TB in relation to sex. Methods: We generated a nationwide TB registry database and assessed the effects of body mass index (BMI) on mortality in patients with pulmonary TB. The cause of death was further classified as TB-related or non-TB-related deaths. First, logistic regression analysis was performed to assess the association between BMI (a continuous variable) and mortality, and subgroup analyses of the multivariable logistic regression model were performed separately in male and female patients. Second, we categorized BMI into three groups: underweight, normal weight, and overweight, and assessed the impact of being underweight or overweight on mortality with reference to normal weight. Results: Among 9,721 patients with pulmonary TB, the mean BMI was 21.3 ± 3.4; 1,927 (19.8%) were underweight, and 2,829 (29.1%) were overweight. In multivariable logistic regression analysis, mortality was significantly increased with the decrement of BMI (adjusted odds ratio [aOR] = 0.893, 95% confidence interval [CI] = 0.875–0.911). In subgroup analyses, underweight patients had significantly higher odds of mortality, especially TB-related deaths (aOR = 2.057, 95% CI = 1.546–2.735). The association with mortality and male patients was higher (aOR = 2.078, 95% CI = 1.717–2.514), compared with female patients (aOR = 1.724, 95% CI = 1.332–2.231). Being overweight had a significant protective effect against TB-related death only in females (aOR = 0.500, 95% CI = 0.268–0.934), whereas its effect on non-TB-related death was observed only in males (aOR = 0.739, 95% CI = 0.587–0.930). Conclusion: Being underweight was linked to high mortality, whereas being overweight had beneficial effects in patients with pulmonary TB.